Timing Attack: An Analysis of Preliminary Data - Alias, Yasin Fitri; Mat Isa, Mohd Anuar; Hashim, Habibah (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Timing attacks have caused an unprecedented evolution in the present cryptographic era where more and more cryptographic applications are running on embedded systems in a wireless environment. Paul Kocher, a well-known cryptanalyst was the first to successfully implement a timing attack on a cryptosystem. Subsequently many other timing attacks have been recorded while cryptographers tirelessly work on making the schemes more resistant to these and other side channel attacks. In this work, we examine timing information leaked from the computation of g^a (mod p) and observe the timing variations of modular exponential computations by varying the key length as well as the operating frequency of our experimental Raspberry Pi board. We have chosen to compute the algebraic expression on a U-Boot Bare Metal platforms our platform and use the GMP bignum library to compute the numbers which are greater than 64 bit. We believe that the timing variations and patterns can lead to the early extraction of secret information in systems based on modular exponentiation. From our observations, there is a strong correlation of timing patterns when computing keys of the same length while the operating frequency used in the computation only affects the computational delay.